Bridging the Gap: Challenges and Solutions in Online Nephrology Education - Habli, Mohamad M (Journal of Clinical Nephrology, 2024)
The outbreak of COVID-19 has created an unprecedented situation that has accelerated online education in areas like nephrology, which are traditionally served by onsite training. Efforts to educate clinicians remotely provide convenience and flexibility but may leave many open questions when it comes to how well-trained professionals maybe after completing their programs online. This review paper has emphasized the deleterious effects of online nephrology education and identified a number of ways in which it can be problematic such as lack of hands-on training, less patient interface, lack of proper supervision, and inconsistent quality of programs. The ability to make a difference, however, is further restricted by technological barriers and resource constraints. Whilst these programs tend to focus on creating knowledgeable graduates, they often fail to provide the clinical exposure necessary for preparedness. Hybrid programs - which combine online courses with clinical training in person are required to deliver high-quality nephrology care.